2014
DOI: 10.15407/ubj86.03.114
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status and glutathione redox potential of erythrocytes in patients with acute coronary syndrome

Abstract: И зучение редокс-сигналирования и ре-докс-регуляции клеточных процессов становится все более весомым и распро-страненным для определения роли участников внутриклеточных и внеклеточных механизмов регуляции метаболизма, прежде всего в про-цессах свободно-радикального окисления, что основывается на способности биологических си-стем генерировать большее число нерадикаль-ных окислителей, нежели свободных радикалов [1,2]. Интенсивность окислительно-восстанови-тельных процессов отражает тиол-дисульфид-ный обмен, дост… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Significant oxidation of intracellular GSH promotes oxidative damage to proteins and lipids and also endangers the structural integrity and viability of red blood cells. The GSH redox status of erythrocytes not only contributes to the growth of their oxidative potential and increases hemolysis, but also reduces the bioavailability of nitric oxide in zones of oxidative damage [1]. The histamine had a special (more adaptive) effects on the antioxidant system of red blood cells on the 7 th day of the experiment.…”
Section: State Of the Antioxidant Protection System In Rats Erythrocymentioning
confidence: 97%
See 3 more Smart Citations
“…Significant oxidation of intracellular GSH promotes oxidative damage to proteins and lipids and also endangers the structural integrity and viability of red blood cells. The GSH redox status of erythrocytes not only contributes to the growth of their oxidative potential and increases hemolysis, but also reduces the bioavailability of nitric oxide in zones of oxidative damage [1]. The histamine had a special (more adaptive) effects on the antioxidant system of red blood cells on the 7 th day of the experiment.…”
Section: State Of the Antioxidant Protection System In Rats Erythrocymentioning
confidence: 97%
“…At the same time, these cells act as a circulating inactivator (sink) of products of oxidative and nitrosyl stress. In erythrocytes there is a high level of compounds that belong to the antioxidant system of protection: reduced glutathione, thioredoxin, vitamins C and E, superoxide dismutase, thioredoxin reductase, catalase, glutathione peroxidase, glutathione reductase, oxydoreductase of the plasmatic membrane, methemoglobin reductase [1]. Glutathione antioxidant system, which includes glutathione peroxidase, glutathione-S-transferase, glutathione reductase, reduced glutathione, prevents the accumulation of toxic products of lipid peroxidation, plays an important role in detoxification, degradation and excretion of heterologous organic substances from the body [2].…”
Section: State Of the Antioxidant Protection System In Rats Erythrocymentioning
confidence: 99%
See 2 more Smart Citations
“…Although erythrocyte has its own pathway, both enzymatic and nonenzymatic, acting as an antioxidative mechanism to protect and counteract those generated ROS [2], the imbalance production of ROS and antioxidant on erythrocyte causes a number of cardiovascular diseases such as acute coronary syndrome [3], hypercoagulation [4], endothelial cell dysfunction [5], and diabetic induced cardiovascular defects [6]. Several studies have suggested that fruit, vegetables, and cereals together with herbs may alleviate or prevent oxidative stress on erythrocyte [710].…”
Section: Introductionmentioning
confidence: 99%